Ways of being : animals, plants, machines : the search for a planetary intelligence - Bridle, James (Picador, 2023)
"Artist, technologist, and philosopher James Bridle's Ways of Being is a brilliant, searching exploration of different kinds of intelligence--plant, animal, human, artificial--and how they transform our understanding of humans' place in the cosmos"--